E-NTPDase activity on lymphocytes triggers a pro-inflammatory action in experimental leptospirosis - Tonin A.A. (2014)
Leptospirosis has recently come to international attention as a globally important reemerging infectious disease since it is a major public health issue in many countries with number of severe leptospirosis being estimated at more than one million per year. Although major progress has been made in the basic research of leptospirosis, the pathogenesis and other aspects remain to be elucidated. On the other hand, the participation of the purinergic system in the inflammatory response is well documented in several diseases. Therefore, the aim of this study was to evaluate the E-NTPDase activity in lymphocytes of Wistar rats experimentally infected with Leptospira interrogans serovar icterohemorrhagiae and its relation with the disease's pathogenesis. For this purpose, 24 adult male Wistar rats were divided in two groups: A, not infected rats (subgroups A1 and A2); B, infected rats (subgroups B1 and B2), which were intraperitoneally inoculated (day 0) with 2 × 108 leptospires/animal. Blood samples were collected on days 15 (A1 and B1) and 30 PI (A2 and B2) to separation of lymphocytes and analysis of E-NTPDase activity of this cell. It observed an increase in E-NTPDase activity when tested the ATP substrate on lymphocytes on day 15 PI and a reduction of its activity when tested the ADP substrate on day 30 PI. The correlation among the infection and E-NTPDase activity leads us to suggest the existence of a pro-inflammatory action due to the compensatory mechanism during the leptospirosis infection, initially due to the actions of ATP, which usually is involved in a pro-inflammatory response, followed by a protective action of ADP or a downregulation attempt of the immune response against the infection. © 2013 Springer-Verlag London.